2015
DOI: 10.2528/pier15010802
|View full text |Cite
|
Sign up to set email alerts
|

PROPAGATION OF PARTIALLY COHERENT BEAM IN TURBULENT ATMOSPHERE: A REVIEW (Invited Review)

Abstract: Partially coherent beam is preferred in many applications, such as free-space optical communications, remote sensing, active laser radar systems, etc., due to its resistance to the deleterious effects of atmospheric turbulence. In this paper, after presenting a historical overview on propagation of optical beams in turbulent atmosphere, we describe the basic theory for treating the propagation of optical beams in turbulent atmosphere and we mainly introduce recent theoretical and experimental developments on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(66 citation statements)
references
References 130 publications
0
66
0
Order By: Relevance
“…The case of a partial coherence was also studied in [17], [18]. Recent theoretical and experimental developments on propagation of partially coherent beams in a turbulent atmosphere were discussed in [19]. There are several analytical approaches explaining behavior of the scintillation index in the case of strong turbulence [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The case of a partial coherence was also studied in [17], [18]. Recent theoretical and experimental developments on propagation of partially coherent beams in a turbulent atmosphere were discussed in [19]. There are several analytical approaches explaining behavior of the scintillation index in the case of strong turbulence [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, partially coherent beams with different types of correlation, including Gaussian Schell-model arrays, 4 multi-Gaussian correlated Schell-model beams, 5 and cosine-Gaussian Schell-model beams 6,7 have been produced. Further to this, the propagation of partially coherent beams in atmospheric turbulence, 8,9 oceanic turbulence, [10][11][12] and isotropic random media 13 has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the propagation properties of a laser beam in turbulent atmosphere [1]. It is found that the intensity and spreading of a laser beam are affected by atmospheric turbulence [2][3][4][5][6][7][8], and the laser beam with a vortex has been widely studied, due to its potential applications in free-space laser communication.…”
Section: Introductionmentioning
confidence: 99%